2022
DOI: 10.1002/path.5860
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps drive epithelial–mesenchymal transition of human colon cancer

Abstract: Neutrophil extracellular traps (NETs) are extracellular structures, composed of nuclear DNA and various proteins released from neutrophils. Evidence is growing that NETs exert manifold functions in infection, immunity and cancer. Recently, NETs have been detected in colorectal cancer (CRC) tissues, but their association with disease progression and putative functional impact on tumourigenesis remained elusive. Using high-resolution stimulated emission depletion (STED) microscopy, we showed that citrullinated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 42 publications
(55 reference statements)
1
48
0
Order By: Relevance
“…High resolution stimulated emission depletion (STED) microscopy was used to detect citrullinated NETs frequently recurring in tissue biopsies from patients with colon cancer. Using anti-DNA antibodies directed to extracellular chromatin, the authors distinguished between condensed and compacted chromatin inside neutrophils with a healthy appearance and ejected decondensed DNA displaying the typical characteristic of NETs [ 106 ].…”
Section: Methods To Detect Nets In Tissue Samplesmentioning
confidence: 99%
“…High resolution stimulated emission depletion (STED) microscopy was used to detect citrullinated NETs frequently recurring in tissue biopsies from patients with colon cancer. Using anti-DNA antibodies directed to extracellular chromatin, the authors distinguished between condensed and compacted chromatin inside neutrophils with a healthy appearance and ejected decondensed DNA displaying the typical characteristic of NETs [ 106 ].…”
Section: Methods To Detect Nets In Tissue Samplesmentioning
confidence: 99%
“…Interestingly, NETs have been detected in e.g. , colon cancer and they may participate in processes such as mesenchymal-epithelial transition ( 59 ). Our conclusion that the citrullination of matrisome proteins in cancer is mainly related to inflammation is based on the following facts: Firstly, analysis of cancer proteomics data sets revealed that many of the most frequently citrullinated matrisome proteins, such as fibrinogen and fibronectin, are also abundantly citrullinated in e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Other pathways besides NETs-DNA may also damage lung epithelial cells, such as NETs mediating inflammasome activation and IL-1β secretion from monocytes and causing airway epithelial cell injury, and NETs modify and regulate lung injury by activating ferroptosis in alveolar epithelial [65][66][67]. Additionally, NETs are associated with the development of lung fibrosis after COVID-19, because NETs induce the downregulation of the epithelial marker E-cadherin and the upregulation of the mesenchymal marker α-SMA in pulmonary epithelial cells [68][69][70][71]. Exposure to butyl benzyl phthalate (BBP), a widely used plasticizer, has been linked to asthma and impaired lung functions [72,73].…”
Section: Nets Drive Lung Epithelial Injury and Pulmonary Fibrosismentioning
confidence: 99%